2021
DOI: 10.1021/acsearthspacechem.0c00317
|View full text |Cite
|
Sign up to set email alerts
|

Observation of N2O5 Deposition and ClNO2 Production on the Saline Snowpack

Abstract: Nitryl chloride (ClNO2), a precursor to highly reactive chlorine radicals and a reservoir for nitrogen dioxide (NO2), is formed from the reaction of chloride with N2O5, which has a longer atmospheric lifetime during the winter. Previous field observations, modeling, and laboratory ice flow tube results led to the hypothesis that saline snow is a source of ClNO2 following the deposition of dinitrogen pentoxide (N2O5). Due to the widespread use of road salt (primarily halite) and its deposition to the snowpack, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(55 citation statements)
references
References 88 publications
(223 reference statements)
6
49
0
Order By: Relevance
“…ClNO2 flux over snow-covered ground, and snow chamber experiments showed that synthesized N2O5 reacted with the local saline snow to produce ClNO2 (McNamara et al, 2021). This finding is also consistent with the laboratory study by Lopez-Hilfiker et al (2012), which showed that N2O5 can react on halide-doped ice surfaces to produce ClNO2.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…ClNO2 flux over snow-covered ground, and snow chamber experiments showed that synthesized N2O5 reacted with the local saline snow to produce ClNO2 (McNamara et al, 2021). This finding is also consistent with the laboratory study by Lopez-Hilfiker et al (2012), which showed that N2O5 can react on halide-doped ice surfaces to produce ClNO2.…”
Section: Discussionsupporting
confidence: 87%
“…5a). This is consistent with measurements of similar net negative (deposition) fluxes of N2O5 over both snow-covered and bare ground (McNamara et al, 2021). In contrast, Figure 5b shows significantly higher (p<0.05, t-test) average ClNO2 mole ratios observed over snow-covered ground at 19:30-22:00, 23:00-00:00, 01:00-01:30, 03:00, and 07:30.…”
Section: Effects Of Ground Coversupporting
confidence: 88%
See 3 more Smart Citations